Dinamika Kelompok Belajar dalam Kelas: Tinjauan Literatur tentang Konsep, Karakteristik, Pembentukan, dan Manajemen Konflik - Cinta Aprilia Putri; Elsa Pramudita; Wiwin Luqna Hunaida (Lembaga Pengembangan Kinerja Dosen, 2026)
Group-based learning in the classroom plays a vital role in enhancing social interaction, individual responsibility, as well as students' critical thinking and collaborative skills. However, its implementation often faces challenges such as the dominance of certain members, social loafing, low participation, and interpersonal conflicts that hinder group effectiveness. This study aims to comprehensively examine the dynamics of learning groups by integrating four key aspects: the concept of group dynamics based on the Tuckman model, the characteristics of effective groups in cooperative learning, group formation techniques, and conflict management strategies. The research utilizes a qualitative approach with a literature study method, analyzing 25 sources including nationally accredited journals, academic books, and theses published between 2020 and 2024. Data analysis was conducted through reduction, thematic classification, content analysis, and conceptual synthesis. The results indicate that effective group dynamics can be achieved through the Tuckman stages, the application of the five elements of cooperative learning, the selection of appropriate group formation techniques with risk mitigation, and the implementation of the Thomas-Kilmann conflict management styles.The scientific contribution of this research is the development of an integrative model based on these four aspects, which serves as a conceptual framework to strengthen collaborative learning practices in the classroom. Practical implications include the formation of ideal groups consisting of 4–5 students, the establishment of initial group contracts, the use of dual assessment rubrics (individual and group), and peer evaluation mechanisms to enhance accountability and reflection.